What Happened to the Bondholding Class? Public Debt, Power and the Top One Per Cent (Preprint) - Sandy Brian Hager (New Political Economy, 2014)
In 1887 Henry Carter Adams produced a study demonstrating that the ownership of government bonds was heavily concentrated in the hands of a 'bondholding class' that lent to and, in Adams's view, controlled the government like dominant shareholders control a corporation. The interests of this bondholding class clashed with the interests of the masses, whose burdensome taxes financed the interest payments on government bonds. Since the late nineteenth century there has been plenty of debate about the ownership of the public debt. But the empirical evidence offered to support the various arguments has been scant. As a result, political economists have few answers to questions first raised by Adams over a century ago: how has the pattern of public debt ownership changed? Can we still speak of a powerful 'bondholding class'? Does public debt redistribute income from taxpayers to public creditors? This article develops a new framework to address these questions. Anchored within a 'capital as power' approach, the research indicates a staggering pattern of concentration in the ownership of US public debt in the hands of the top one per cent of US households over the past three decades. Accordingly, the bondholding class is still alive and well in contemporary US capitalism.
Keywords: 330; public debt; power; distribution; redistribution; bondholding class; inequality; top one per cent